Revolutionizing Writing: The Impact of Technology on Enhancing Students' Writing Skills - Friatin, Lilies Youlia (JALL (Journal of Applied Linguistics and Literacy), 2025)
The use of artificial intelligence (AI) in writing instruction has introduced new opportunities for enhancing students’ creativity and engagement. This study explores students’ perceptions of Canva AI Magic Writer in developing descriptive writing skills. Using a qualitative case study approach, data were collected from 30 university students through a questionnaire. The findings reveal that most students found AI helpful in overcoming writer’s block and improving descriptive details. However, some expressed concerns about originality and the potential loss of personal voice. While AI tools enhance creativity and motivation, their use should be balanced with strategies that promote independent writing skills. This study recommends integrating AI with structured guidance to maximize its benefits while fostering originality and critical thinking.